Towards parenthood : preparing for the changes and challenges of a new baby - Milgrom, Jeannette (Camberwell, Vic. : ACER Press, 2009)
Towards Parenthood aims to assist soon-to-be and current parents manage the complex demands of parenting and strengthen the parent-infant relationship and the couple relationship. The book covers expectations of parenthood, skills in coping, problem-solving, enhancing self-esteem, assertive communication, bonding with your baby and understanding your baby's cues.
Cover; Copyright; Contents; Preface; Acknowledgements; About the authors; 1 Towards motherhood; 2 Towards fatherhood; 3 We're expecting! Preparing for parenthood; 4 Caring for yourself is caring for your baby; 5 From lovers to parents: managing relationship changes; 6 Keeping some balance in your life; 7 Healthy thinking, healthy self; 8 Caring for your newborn baby; 9 Welcome to 'The Club'!; Appendices; References; Further reading.
Includes bibliographical references (pages 141-145).
Print version record.
eBooks on EBSCOhost
Keywords: Infants; Infants -- Care; Parenting; Parent and infant; Parents; Psychology; Social psychology; Sociology; Social sciences; Parents; Popular Works; Education; Psychology; Publication Formats; Persons; Nuclear Family; Behavioral Sciences; Anthropology, Education, Sociology and Social Phenomena; Family; Named Groups; Publication Characteristics; Behavioral Disciplines and Activities; Psychology, Social; Sociology; Psychiatry and Psychology; Behavior and Behavior Mechanisms; Social Sciences; Infant Care; Parenting; Social Sciences; Family & Marriage; Sociology & Social History; Nourrissons -- Soins; Rôle parental; Parents et nourrissons; Parents; Psychologie; Familles; Sciences du comportement; Psychologie sociale; Sociologie; Sciences sociales; psychology; behavioral sciences; social psychology; sociology; social sciences; parents; FAMILY & RELATIONSHIPS -- Life Stages -- Infants & Toddlers; Sociology; Social sciences; Social psychology; Psychology; Parents; Infants; Infants -- Care; Parent and infant; Parenting